Dendrimers: Advancements and Potential Applications in Cancer Diagnosis and Treatment-An Overview - Andreea Crintea; Alexandru Cătălin Motofelea; Alina Simona Șovrea; Anne-Marie Constantin; Carmen-Bianca Crivii; Rahela Carpa; Alina Gabriela Duțu (MDPI AG, 2023)
Cancer is a leading cause of death worldwide, and the main treatment methods for this condition are surgery, chemotherapy, and radiotherapy. These treatment methods are invasive and can cause severe adverse reactions among organisms, so nanomaterials are increasingly used as structures for anticancer therapies. Dendrimers are a type of nanomaterial with unique properties, and their production can be controlled to obtain compounds with the desired characteristics. These polymeric molecules are used in cancer diagnosis and treatment through the targeted distribution of some pharmacological substances. Dendrimers have the ability to fulfill several objectives in anticancer therapy simultaneously, such as targeting tumor cells so that healthy tissue is not affected, controlling the release of anticancer agents in the tumor microenvironment, and combining anticancer strategies based on the administration of anticancer molecules to potentiate their effect through photothermal therapy or photodynamic therapy. The purpose of this review is to summarize and highlight the possible uses of dendrimers regarding the diagnosis and treatment of oncological conditions.